Is it Possible to Weave 8.end Satin with 5 Rods on a Warp-weighted Loom? - Antoinette M. Olsen (EXARC Journal)
Back in 2020, I wrote an article entitled The Shroud of Turin and the Extra Sheds of Warping Threads (Olsen, 2020). When I was studying the weaving theory, I realised that it might be possible to weave 8-end satin with five rods on the warp-weighted loom. To date, I have not encountered any historical find showing satin woven on a warp-weighted loom eighter, nor have I heard or read about anybody else undertaking this, so I decided to try to test it.